Extracellular Vesicle-Associated MicroRNA-138-5p Regulates Embryo Implantation and Early Pregnancy by Adjusting GPR124 - Hsien-Ming Wu; Tzu-Chi Lo; Chia-Lung Tsai; Liang-Hsuan Chen; Hong-Yuan Huang; Hsin-Shih Wang; John Yu (MDPI AG, 2022)
Functional embryo-maternal interactions occur during the embryo implantation and placentation. Extracellular vesicles with microRNA (miR) between cells have been considered of critical importance for embryo implantation and the programming of human pregnancy. MiR-138-5p functions as the transcriptional regulator of G protein-coupled receptor 124 (GPR124). However, the signaling pathway of miR138-5p- and GPR124-adjusted NLRP3 inflammasome activation remains unclear. In this study, we examine the roles of the miR138-5p and GPR124-regulated inflammasome in embryo implantation and early pregnancy. Human decidual stromal cells were isolated from the abortus tissue and collected by curettage from missed abortion patients and normal pregnant women at 6- to 12-week gestation, after informed consent. Isolated extracellular vesicles from decidua and decidual stromal cells were confirmed by transmission electron microscopy (TEM). Next-Generation Sequencing (NGS) and microarray were performed for miR analysis. The predicated target genes of the differentially expressed miR were analyzed to identify the target genes and their pathway. We demonstrated the down-regulation of miR-138-5p and the overexpression of GPR124 in spontaneous miscarriage compared to normal pregnancy. We also showed the excessive activation of the NLRP3 inflammasome in spontaneous miscarriage compared to normal pregnancy. Here, we newly demonstrate that the miR-138-5p and GPR124-adjusted NLRP3 inflammasome were expressed in extracellular vesicles derived from decidua and decidual stromal cells, indicating that the miR-138-5p, GPR124 and NLRP3 (NACHT, LRR, and PYD domains-containing protein 3) inflammasome have a potential modulatory role on the decidual programming and placentation of human pregnancy. Our findings represent a new concept regarding the role of extracellular vesicles, miR-138-5p, GPR124, and the NLRP3 inflammasome in normal early pregnancy and spontaneous miscarriage.